Tailoring the structural and optical characteristics of InGaN/GaN multilayer thin films by 12 MeV Si ions irradiations. (15th June 2017) - Ahmad, Ishaq; Madhuku, M.; Sadaf, Adeela; Khan, Shakil; Hussain, Javaid; Ali, Awais; Wan, D.; Ilyas, S.Z.; Mola, G.; Waheed, Abdul; Rasheed, Muhammad Asim
Abstract: In this study, the influence of Si ions irradiations (12 MeV energetic) on structural and optical characteristics of InGaN/GaN thin film has been investigated. Irradiation was performed at different Si ions fluences in the range of 1×10 13 to 1×10 15  ions/cm 2 . X-ray diffraction (XRD) pattern of pristine film indicates only the (0 0 2) oriented crystallites of InGaN while the irradiated films patterns showed other phases (InN and GaN) as well. Ion irradiations at different dose rates have shown no or negligible effect on grain size of InGaN except a shift in the peak position which demonstrates the development of tensile stresses. The existence of other phases in the irradiated films patterns is the indication of InGaN phase separation. Defects produced due to irradiation were also confirmed from peak shifting and appearance of new peak at 669 cm −1 in Raman spectra. A decrease in optical bandgap with the increase of ion irradiation dose rate is being reported in this work.